DIABETES SELF-MANAGEMENT DAN KEPATUHAN MINUM OBAT PADA PASIEN DIABETES MELITUS DALAM KONTEKS KELUARGA - Dodik Arso Wibowo; Andika Siswoaribowo (Jurnal Keperawatan Malang, 2026)
Background: Type 2 DM, also known as non-insulin dependent can be prevented through healthy lifestyle changes and medication adherence. Diabetes Self Management focuses on improving the patient's ability to optimize blood sugar levels including the importance of taking medication regularly Purpose: The purpose of the study was to determine the relationship between Diabetes Self Management and medication adherence in terms of family support in type 2 DM patients at the Bendo Health Center Methods: population consisted of 112 patients with type 2 diabetes mellitus at Bendo Primary Health Center. A total of 34 respondents were selected using purposive sampling, with sample size calculated using the Lemeshow formula. The research instruments included the Diabetes Self-Management Questionnaire (DSMQ) to assess patients’ diabetes self-management and the Morisky Medication Adherence Scale-8 (MMAS-8) to measure medication adherence. Data were analyzed using the Spearman’s rho correlation test Result: The results showed that most respondents (79.4%) had good diabetes self-management, and more than half (52.9%) demonstrated high medication adherence. The Spearman’s rho test yielded a p-value of 0.001 (<0.05), indicating a significant association between diabetes self-management and medication adherence among patients with type 2 diabetes mellitus. The correlation coefficient (r = 0.537) indicates that better diabetes self-management is associated with higher medication adherence, with a moderate strength of correlation Implication: Type 2 DM patients are expected to be able to manage themselves well so that patients can be obedient to taking medication as an effort to prevent the risk of complications   Keywords: Type 2 Diabetes Mellitus; Diabetes Self-Management; Medication Adherence; Family Support